Comprehensive evaluation and reservoir classification in the Quan 3 Member of the Cretaceous Quantou Formation in the Fuxin Uplift, Songliao Basin - Zhang, Qin; Zhang, Ya-Xiong; Wang, Bo-Han; Yin, Shuai; Wu, Xin-Song; Yuan, Cheng-Shuai (Frontiers in Earth Science, 2022)
Continental tight oil sandstone reservoirs are developed in the Cretaceous Quentou Formation in the Songliao Basin, China. At present, there is still a lack of research on the reservoir microstructure, reservoir physical properties, and the division scheme of reservoir types in the Quan 3 Member of the Quanzhou Formation. Therefore, in this paper, taking the Quan 3 Member in the Fuxin Uplift Belt of the Songliao Basin as an example, the microscopic pore structure characteristics of tight oil sandstones have been systematically studied, and the classification standard of tight sandstones has been formulated. Furthermore, the sweet spots of the main production layers are predicted. The results show that the sedimentary facies of the I sand group in the Quan 3 Member in the study area are shallow water delta facies. The lithology of the target layer is mainly feldspar lithic fine sandstone, and calcareous sandstone is locally developed in some layers. Moreover, the pore types of the target layer are mainly dissolved intergranular and intragranular pores, followed by primary intergranular pores, and micro-fractures are occasionally seen. According to the mercury intrusion test results, the pore-throat structures of the reservoir in the Quan 3 Member are divided into four types: (1) small-pore medium-throat type (point bar and delta distributary channel), (2) small-pore micro-throat type (point bar), (3) small-pore micro-throat type (natural levee), (4) micro-pore micro-throat type (river floodplain and inter-tributary bay). The lower limits of the physical properties of the effective reservoirs in the Quan 3 Member has been determined: porosity is 10%, permeability is 0.1 mD. Finally, combined with mercury intrusion curves, physical property tests and sedimentary facies characteristics, the classification standard of the Quan 3 Member reservoirs was formulated. For the I sand group, the sweet spots of the Type I reservoirs are mainly developed in the Fuyu Oilfield in the southeast areas. The sandstones in this area suffered less compaction, and mainly developed primary pores and secondary pores formed by late dissolution.